Eosinophilic Fasciitis with Concurrent Necrobiotic Granulomatous Dermatitis Related to Checkpoint Inhibition Therapy - Adeeb Haroon; Joseph Tadros; Emily H. Smith (Journal of Immunotherapy and Precision Oncology, 2022)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer therapeutics. However, loss of physiologic tolerance in few cases has triggered rare and novel immune-related adverse events (irAEs). Eosinophilic fasciitis, an infrequently reported diffuse scleroderma-like entity, has been associated with ICI therapy. We report a case of a patient with metastatic melanoma treated with nivolumab who developed eosinophilic fasciitis with concurrent granulomatous dermatitis and lymphadenitis, the latter of which mimicked melanoma recurrence radiographically. Furthermore, this patient had a severe presentation that subsequently proved to be treatment-resistant to both corticosteroid and steroid-sparing therapies. To our knowledge, eosinophilic fasciitis has not been reported concurrently with granulomatous dermatitis in literature. We provide a narrative of this case and a review of therapeutic approaches for severe or refractory irAEs. With the increasing popularity of ICI therapy, we believe it is essential for clinicians to identify novel irAEs and be aware of treatments as late recognition could prove fatal.